Machine Learning Models for Classification of Anemia from CBC Results: Random Forest, SVM, and Logistic Regression - Muhammad Rafli, Aditya; Teguh, Sutanto; Haldi, Budiman; M.Rezqy, Noor Ridha; Usman, Syapotro; Noor, Azijah (INTI International University, 2024)
In an effort to increase diagnostic efficiency and accuracy, this work investigates the application of machine learning models Random Forest, SVM, and Logistic Regression for the categorization of anemia. Hematocrit and hemoglobin levels were included in the dataset, which was divided into training and testing sets. Using CatBoost, Random Forest outperformed SVM (82.1%) and Logistic Regression (75.1%) with the greatest accuracy (99.2%). SVM and Logistic Regression work well with simpler data, while Random Forest performs best with intricate medical datasets, which makes it perfect for applications involving the detection of anemia.